2022
DOI: 10.1021/acs.chemrestox.2c00100
|View full text |Cite
|
Sign up to set email alerts
|

BML-257, a Small Molecule that Protects against Drug-Induced Liver Injury in Zebrafish

Abstract: The use of many essential drugs is restricted due to their deleterious effects on the liver. Molecules that can prevent or protect the liver from drug-induced liver injury (DILI) would be invaluable in such situations. We used a transgenic line in zebrafish with a hepatocyte-specific expression of bacterial nitroreductase to cause temporally controlled liver damage. A whole organism-based chemical screen using the transgenic line identified BML-257, a potent small molecule AKT inhibitor, that protected the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…It was demonstrated that the administration of 10 mM INH between 3-4 dpf resulted in liver size decrease (Jagtap et al, 2022). Another study reported induction of apoptosis upon exposure to 6 mM INH between 4-5 dpf (Higuchi et al, 2021).…”
Section: Isoniazid-induced Liver Enlargement Only At 5-7 Dpf Stagementioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the administration of 10 mM INH between 3-4 dpf resulted in liver size decrease (Jagtap et al, 2022). Another study reported induction of apoptosis upon exposure to 6 mM INH between 4-5 dpf (Higuchi et al, 2021).…”
Section: Isoniazid-induced Liver Enlargement Only At 5-7 Dpf Stagementioning
confidence: 99%
“…DILI remains one of the most challenging issues in the discovery and pre/postmarketing stages of drug development (Andrade et al, 2019). Zebrafish larva due to it being time and costeffective, has attracted interest as an in vivo model for prediction of a drug candidate's hepatotoxicity potential (Jagtap et al, 2022). The rapid maturation of the liver within 5 days post fertilization (dpf), transparency of the larvae, easy application of test compounds, and the possibility for medium-throughput live imaging are among attractive features of zebrafish (Chu & Sadler, 2009;Katoch & Patial, 2021;Vliegenthart et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of bacterial nitroreductase gene in hepatocytes is used for targeted ablation of liver cells via exposure to prodrug metronidazole [55]. Recently this tool has been used to identify hepatoprotective small molecules in a screen and BML-257, an AKT inhibitor, was found to provide protection against liver damage caused by acetaminophen (APAP) and isoniazid [63]. Moreover, according to a recent review, the role of ferroptosis in DILI, when compared to other liver diseases, remains relatively unexplored with most of the research being based on APAP induced DILI [64].…”
Section: Reporter Transgenic Zebrafish Lines For the Accurate Assessm...mentioning
confidence: 99%
“…It is thought that depletion of glutathione (GSH) by NAPQI causes oxidative stress, resulting in hepatotoxicity. APAP toxicity has also been reported in adult zebrafish and larvae [ 15 , 16 ]. North et al [ 17 ] showed that APAP caused reduction of liver size through inducing apoptosis in larval zebrafish and that the combination of prostaglandin E2 (PGE2) and N -acetylcysteine (NAC), a precursor of GSH, reversed APAP toxicity in the liver.…”
Section: Introductionmentioning
confidence: 99%